'The emperor lost his clothes': Rupert Murdoch, News of the World and journalistic boundary work in the UK and USA. (May 2014) - Carlson, Matt; Berkowitz, Dan
Episodes of journalistic deviancy become moments of reflection for the journalistic interpretive community, at times assuming international proportions. This study examines the construction of appropriate journalistic norms through reactions to the phone hacking scandal that led to the abrupt closure of the British Sunday tabloid the News of the World on 10 July 2011. A comparison of reactions in US and UK newspapers reveals how boundary work articulates appropriate practices through defining deviant behavior. Rather than isolating the troubles to a single newsroom, what emerges is a form of synecdochic deviancy in which the significance of the scandal expands to larger normative questions among journalists in both nations.